Building Business Independence: A Creative Business Workshop for the Indonesian Migrant Community in Malaysia - Wardana, Hendrata Yudha; Arsyad, Abd. Rahim; Surya, Muhammad Arsyadillah; Surya , Ade Anastasya; Dewi , Putri Rosmala; bin Omar , Ismail; Kunia Annisa , Nurul Ulfa; Mustofa , M. Zazili (Kawanad : Jurnal Pengabdian kepada Masyarakat, 2026)
This International Community Service (PKM) activity aims to increase the economic independence of the Indonesian migrant community, which is part of the Persatuan Anak Rantau Indonesia (PARI) in Malaysia, through a creative business workshop based on community empowerment. This program is motivated by the still limited entrepreneurial literacy, structured business planning, and economic networking among community members. The activity is organized by the ASEAN Academic Association (ASEANACA) under the auspices of the Lampung Islamic College of Economics and Business (STEBI), using a participatory approach based on partners' needs. The materials cover identifying micro-business opportunities, developing a Business Model Canvas, digital marketing strategies, and financial management based on Islamic economic principles. The implementation methods include interactive workshops, group discussions, and mentoring in business plan development. The outputs include draft business plans, training modules, increased entrepreneurial literacy, and the inauguration of the PARI Kuala Lumpur management as a form of community institutional strengthening. This program is expected to encourage the formation of productive community-based businesses and strengthen the economic network of the Indonesian diaspora in Malaysia.